A multicriteria decision-making approach for prioritizing renewable energy resources for sustainable electricity generation in Benin. Issue 1 (31st December 2023) - Akpahou, Romain; Odoi-Yorke, Flavio
Abstract: Benin's rapid population, economic, and industrial growth will increase energy demand. Hence, Benin's government is keen to increase its power capacity to meet future demand. Renewable energy sources are significant options that governments could explore when developing their sustainable energy strategies. Prioritizing energy sources for a country's sustainable development requires a decision-making process. In this study, multicriteria decision-making (MCDM) methods are used to prioritize alternatives such as solar photovoltaic (PV), concentrated solar power (CSP), wind energy, hydropower, and bioenergy suitable for sustainable electrification in Benin. The study employed eighteen (18) criteria classified under the four pillars of sustainability (technical, social, economic, and environmental) to evaluate the alternatives. Thereafter, the criteria importance through inter-criteria correlation (CRITIC) and entropy methods, which were employed to compute criteria weights and incorporated into the evaluation based on distance from average solution (EDAS) method to rank the alternatives. The findings from the EDAS rankings show that solar PV is the optimal alternative, ranking in the first position, followed by wind energy in the second position. CSP, hydropower, and bioenergy rank in the third, fourth, and fifth positions. In addition, EDAS findings correlated fully with those of other MCDM approaches evaluated on the same decision matrix. This indicates that solar PV is Benin's optimal technology for sustainable electricity generation. The study's findings are critical for policymakers developing Benin's renewable energy sector.